Implementation Of Statement Of Financial Accounting Standards (SFAS) 112 Concerning Wakaf Accounting At The Ar-Rasyid Nabarang Baya Foundation - Gina Sakinah; Fauziah Khoirunnisa; Ade Ponirah; Syahwa Natasya Sugari; Zahra Rafiatuddinna Namilah (Risalah Iqtishadiyah, 2024)
This research aims to analyze the implementation of SFAS 112 concerning waqf accounting at the Ar-Rasyid Nabarang Baya Foundation. This research uses qualitative research methods with a descriptive approach. In this research, some information aims to describe systematically, factually, and accurately the application of SFAS 112 in the Financial Reports of the Ar-Rasyidi Nabarang Baya Foundation; the research only applies to the area studied. It uses primary data and secondary data. The data Analysis technique in this research is descriptive analysis with stages of data reduction analysis, data presentation, and conclusion. The results of the research show that the recognition aspect was found, namely that in the financial reports of the Ar-Rasyidi Nabarang Baya Foundation, it did not record waqf assets that were still in the form of we'd or promises in the financial reports; this was felt to be uncertain in the waqf. The Ar-Rasyidi Foundation's financial report does not admit any liabilities. In the measurement aspect, it was found that the measurement of waqf assets in the form of money and land in the financial statements of the Ar-Rasyidi Nabarang Baya Foundation was by SFAS 112. In the disclosure aspect, the Ar-Rasyidi Nabarang Baya Foundation has disclosed its financial reports in the Notes to Financial Reports.